Sex differences in erythrocyte fatty acid composition of first-diagnosed, drug-naïve patients with major depressive disorders - Wang, Lu; Liu, Ting; Guo, Jimin; Zhao, Tingyu; Tang, Hui; Dong, Fang; Wang, Chuanyue; Chen, Jindong; Tang, Mimi (Frontiers in Pharmacology, 2023)
Background Since depression, sex hormones, and fatty acid status are interrelated, it is important to understand their relationships. In this study, we aimed to investigate sex differences in erythrocyte membrane fatty acid composition among first-diagnosed, drug-naïve patients with major depressive disorders.2 Methods The study included 139 individuals with first-diagnosed, drug-naïve depression (male/female = 48/91) and 55 healthy controls (male/female = 24/31). The levels of erythrocyte membrane fatty acids were analyzed to compare the difference between males and females in both patients with depression and healthy controls, as well as to study their correlation with depressive symptoms.In first-diagnosed, drug-naïve patients with major depressive disorders, sex disparities were observed in the levels of erythrocyte saturated fatty acids (SFAs) and n-6 PUFAs (such as C18:0, C20:4n6, and C22:4n6), where higher levels were evident in females compared to males.We found a noteworthy correlation between fatty acid levels and depressive symptoms, in which there is a significant association between female patients and depression but a weaker association between male patients and depression.Our findings demonstrate higher levels of n-6 PUFAs and SFAs in female patients with depression. The relationship between fatty acid composition and depressive symptoms was more prominent in females than males. These findings highlight the significance of considering sex as a crucial and interconnected factor in future investigations and potential adjunctive treatment for mood disorders by targeting fatty acid metabolism.